PSA testing and digital rectal examination in New Zealand - Mary Jane Sneyd; Brian Cox; Charlotte Paul; David C.G. Skegg (Elsevier, 2003)
Abstract Objective: To investigate the use of digital rectal examination and prostate specific antigen (PSA) testing in a population‐based sample of men in New Zealand. Methods: A random selection of men aged 40-74 years, weighted by age, was chosen from the general electoral roll of New Zealand. Only men with a telephone who had been married at some time were eligible. Telephone interviews were conducted using a standard questionnaire. Crude and age‐adjusted proportions were calculated. Logistic regression was used to explore associations between socio‐demographic factors and digital rectal examination or PSA testing. Results: Interviews were completed for 85% of the 1,486 eligible men and analyses were confined to the 1,225 European men. Many more men reported having a digital rectal examination (41%; 95% CI 33.8-48.2) than a PSA test (9%; 95% CI 4.2-14.2). Men in the lowest social class were significantly less likely to have had a digital rectal examination (OR 0.30; 95% CI 0.18-0.50) or PSA test (OR 0.25; 95% CI 0.11-0.60) compared with those in the highest social class. Men with vocational training or no post‐school qualifications were approximately half as likely to report a digital rectal examination or a PSA test compared with men with degrees or diplomas. Conclusions: Although current New Zealand recommendations are that population screening for prostate cancer should not be introduced, many men are still having digital rectal examinations and PSA tests in the absence of symptoms. The frequency of PSA testing is considerably lower than in Australia and appears to be largely influenced by a man's social class.